PROBLEMATIKA PESERTA ANAK DIDIK DAN MASYARAKAT DESA WINONG: (Analisis Penguatan Pendidikan Agama Islam) - Kurnaesih, Uun; M. Sudi, Didih (Staisman Press, 2021)
Islamic religious education does not only exist in a formal educational institution but is also a problem for all elements of society, including families. Problems and challenges that exist in Islamic Religious Education both in learning and its application are multidimensional. You have to face it and find a way out. The purpose of this study is to try to present an overview of the problems and offer solutions in learning Islamic religious education, especially those that exist and occur in Winong Village. In this study the author seeks to discuss the problems of Islamic Religious Education in terms of the scope of education, namely the community, in this case the community in Winong Village. Qualitative research methods with primary and secondary data collection. Data collection is based on information from informants, both written and verbal, researchers collect data by means of observation, in-depth interviews and documentation. Data analysis was carried out during data mining in the field and after data was collected. And secondary sources with a library approach. The results of the research found problems that became a challenge in Islamic Religious Education both as a scientific discipline, educational institution and as a way of life in the life of every human being as a religious being. It is then that Islamic education has the aim of forming a Muslim personality, namely a personality whose all aspects are based on Islamic teachings. If you look at the goals of Islamic Religious Education, it is in line with the goals of human life itself